MYOCARDIAL INFARCTION TYPE 2. MYTH OR REALITY? - V. V. Zhelnov; N. V. Dyatlov; L. I. Dvoretsky (SINAPS LLC, 2016)
According to The Third Definition of Myocardial Infarction there are five types of myocardial infarction depending on pathogenesis. This review provides actual data about myocardial infarction type 2 mechanism including diagnosis management, epidemiological characteristic and patient prognosis. Previously published data shows discordant information about myocardial infarction type 2 frequency, treatment and diagnostic options. Our clinical observation illustrates these severities in diagnosis construction, disease feature in acute period in casual clinical practice.